Peran DPRD Kabupaten Ciamis Dalam Pembentukan Peraturan Daerah Nomor 13 Tahun 2019 Tentang Rencana Pembangunan Jangka Menengah Daerah Kabupaten Ciamis Tahun 2019-2024 - Rizky Firdaus; Hanny Purnamasari (Peneliti.net, 2022)
Regional Regulations are instruments for the administration of regional government established by the House of Representatives (DPRD) and the Regional Government. Therefore, in its formation, it must go through a process of joint discussion with the DPRD. This research focuses on the formation of Regional Regulation Number 13 of 2019 concerning the Regional Medium Term Plan (RPJMD) of Ciamis Regency for 2019-2024 in which the Regional Regulation is a proposed initiative of the Regional Head. However, DPRD also has a role in determining the direction of regional development policies through a discussion process based on general views and proposals from faction members from the economic, infrastructure and environmental aspects. This is a problem to see the extent of the role of DPRD in determining the direction of regional development policies through the RPJMD. This empirical research uses primary data and secondary data using descriptive qualitative methods with an approach that is carried out by reviewing the RPJMD regulations associated with the policy direction strategy. Thus, in this study, the use of role theory based on an acted role indicator related to the legislative function of the DPRD in the formation of the Regional Regulations of the RPJMD. Based on this research, it was found that the DPRD of Ciamis Regency has an anacted role in the process of forming the RPJMD of Ciamis Regency in 2019-2024. This is evidenced by the dominance of the faction in providing proposals and general views at the discussion stage of the RPJMD Regional Regulation. Among them from the economic aspect, namely the National Awakening Party (PKB) faction which provides an overview of the resources that are important factors in encouraging community economic growth, the second from the infrastructure aspect, namely the Democratic Party faction proposing the use of national development projects, and the third environmental aspect, namely the Democrat Party faction. The Prosperous Justice Party (PKS) emphasizes the use of natural resources for sustainable development